Enzymatic extraction of green banana resistant starch for future food preparation: Structural, physicochemical and functional characterization - Shariful Islam; Md. Abdus Satter Miah; Md. Faridul Islam; Khurshida Jahan Tisa; Md. Mahmudul Hassan Mondol (Future Foods, 2024)
The aim of this work was to isolate the resistant starch (RS) from green banana using amyloglucosidase in conjunction with pancreatin intervention and subsequently investigate their physicochemical, structural, functional and antioxidant properties. In vitro, digestibility studies revealed that peeled banana resistant starch (PBRS) and unpeeled banana resistant starch (UBRS) had purity of 87.91% and 89.26%, respectively and PBRS had the highest moisture (6.97%), ash (0.25%), and protein (0.78%) content whereas UBRS exhibited the maximum fat (0.30%), fiber (2.03%) and carbohydrate (91.48%) content. The apparent amylose content (AAC) and total dietary fiber content of extracted RS from both peeled and unpeeled banana showed significant difference (p ≤ 0.05). The AAC was found 48.53% and 43.41% whereas dietary fiber was recorded 15.49% and 17.53% for PBRS and UBRS, respectively. The PBRS demonstrated excellent functional properties and the water absorption capacity, swelling power and solubility were recorded 8.43 g/g, 11.74 g/g and 9.23%, respectively. The scanning electron micrograph showed elongated or rounded shapes particles with smooth surfaces for both samples, and their estimated size fell within the range of 13.1 to 59.6 µm. The prominent X-ray diffraction peaks at 15°, 17° and 23° 2θ values with characteristic B-type crystals further confirmed the purity of extracted RS. The total phenolic (TPC), total flavonoid (TFC), total antioxidant (TAC) and DPPH free radicals scavenging activities data proved the PBRS superior antioxidant potentiality. Therefore, PBRS can be suggested to use as a raw material for future food product development and other relevant fields.